2021
DOI: 10.1111/cbdd.13919
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the detailed structure–activity relationship of coumarins as Monoamine oxidase enzyme inhibitors—An updated review

Abstract: Monoamine oxidases (MAOs) have become a potential target for the treatment and slow down of several neurodegenerative diseases. These are flavoenzymes that are present in the exterior of the mitochondrial membrane (Patil et al., 2013). Members of the monoamine oxidase family of flavoproteins catalyze the breakdown of primary, secondary amines, polyamines, and amino acids, including lysine demethylation in proteins (Gaweska & Fitzpatrick, 2011). MAOs are also found in almost any brain area as well as most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…The coumarin scaffold shows wide industrial applications and medicinal uses, of which a notable example is warfarin, the most common anticoagulant prescribed worldwide [135]. Coumarins (Figure 9 and Table 4) have been proposed as privilege scaffold and focused on as MAO inhibitors [136,137].…”
Section: Mao Inhibitory Activity Of Coumarinsmentioning
confidence: 99%
“…The coumarin scaffold shows wide industrial applications and medicinal uses, of which a notable example is warfarin, the most common anticoagulant prescribed worldwide [135]. Coumarins (Figure 9 and Table 4) have been proposed as privilege scaffold and focused on as MAO inhibitors [136,137].…”
Section: Mao Inhibitory Activity Of Coumarinsmentioning
confidence: 99%
“…The newest marketed FDA-approved drug safinamide and lazabemide (nonmarketed) ( Figure 2 ) are reversible selective MAO-B inhibitors. 40 , 41 Moreover, the isatin small molecule is identified as a reversible MAO enzyme. The PDB IDs 1OJA and 2XFP are two protein 3D structures in MAO-B with the isatin complex.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugation of coumarins with a second pharmacophore is currently gaining attention to access multitarget drugs 30 . Many of such activities are the result of the inhibition of key enzymes by coumarin-containing derivatives 20 , 31–38 , either natural or synthetic; this is due to their peculiar planar structure and to the possibility of establishing strong non-covalent interactions involving the lactone moiety (hydrogen bonding, dipole-dipole) and the aromatic scaffold (π-π and cation-π interactions) 21 . Regarding CAs, the slow inhibition mode observed for coumarins compared to sulfonamido-derivatives suggested that they might behave as suicide inhibitors 39 .…”
Section: Introductionmentioning
confidence: 99%